Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Honda Pada Toko Sekar Sari di Denpasar - Adinata, A.A Made Widia; Suasana, I Gst. Agung Ketut Gede (E-Jurnal Manajemen; Vol 2 No 1 (2013), 2013)
This study aimed to determine the effect of price, palce, and promotion against buyer decision of motorcycle in Sekar Sari Company. The sample amount 100 respondent. Analysis techniques are (F test) and (t test). The test results showed F count simultaneously is greater than F table, it can be concluded that price, palce, and promotion efective significantly against buyer decision of motorcycle in Sekar Sari Company. Adjusted R Square of 88,9%. The test results show that partial asset structure variable (X1) and company size (X3) have a positive and significant impact on capital structure, while profitability (X2) and significant negative effect on capital structure. This is evident from the t value greater than the value of t table   Key Word: market dispersion, decision to buy vehicle